Modern Approach to the Regional Strategic Planning: Main Directions and Tools - Dmitriy Aleksandrovich Abashev; Valery Vitalyevich Yanovskiy (Управленческое консультирование)
The trend of Russian Federation economy development assumes not only almost insulating independence, but also risks of the wrong planning connected with it. Development and deployment of development schemes is caused by need of consolidation of efforts of regions. The purpose of our work - to make the comparative analysis of points of views about the choice of key factors for forming strategic planning model for what we allocated basic groups of theories of regional growth. Strategic planning of the region development, in our opinion, has to include several main positions (the regional economy containing infrastructure system, etc.) which are allocated and analyzed explicitly. As obligatory to inclusion in process of strategic planning in the region we allocated one of groups of factors - regional geographical realities. On the basis of this hypothesis the example of the development scheme is necessary to take into account region zonality, which is in detail discussed in work. Authors also revealed various aspects of the concept «strategic planning». In Europe the main activities within territorial strategic planning are systematized, tools for this at the regional level are classified.